Analisis Faktor-Faktor Strategis yang Mempengaruhi Pengelolahan Sampah di Kota Jambi - Hilsia, Atresha Oktadio; Naswir, M.; Harmes, Harmes (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to analyze the factors that influence waste management in Jambi City through a case study approach and environmental policy implementation. This research uses a mixed method, which combines quantitative and qualitative approaches. Primary data was collected through questionnaires, interviews and direct observation, while secondary data was obtained from document studies such as journals, books, reports and related regulations. Data analysis was carried out using the SWOT technique to evaluate internal and external factors that influence waste management in Jambi City. The research results show that waste management in Jambi City still faces various challenges, including a lack of waste separation at the source and fluctuations in the price of recycled products. Strong regulatory support and local government commitment provide opportunities for better waste management. Advanced waste processing technology and increasing public awareness were also identified as important factors that can support the success of waste management in Jambi City.